Regreso sobre la noción de objeto frontera - Pascale Trompette; Dominique Vinck (Revue d'anthropologie des connaissances)
The article revisits the original publication by Susan L. Star and James R. Griesemer (1989) which founded the notion of the boundary object to rethink the actor-network theory (ANT) from an ecological perspective of collective action and distributed knowledge, considering artefacts. It then looks at the academic career of the concept and what has been used (“interpretative flexibility”) vs. underplayed and forgotten (the incorporation of an invisible infrastructure) of its original conceptualisation. The article proposes to reinvestigate the concept by being careful to maintain the articulation of these two dimensions.